The Era of Cultivating Silkworms and Wrapping Pillows Evaluation of The Effect on The Quality of The Pillow - Elomonov Ro‘zimurod Doniyor o‘g‘li (European Science Publishing, 2023)
This article presents the important agro-technical measures that need to be taken during the feeding of silkworms and cocoon curling. Information is also provided on the nutrients that silkworms need at each age, how much space they need for each age, and the microclimate conditions required. The research work of national and foreign scientists working in this field was also analyzed. The effects of silkworm feeding and cocoon curling on cocoon quality were also studied, and recommendations were given on what to look for when feeding silkworms to obtain quality cocoon raw materials.
Keywords: silkworm, cocoon, cocoon curling period, cocoon quality, mulberry leaf, artificial cocoon, air temperature, relative humidity.